Difficult to quit smoking beyond “nicotine dependence”: a preliminary survey among adult male smokers in Felda Bukit Goh,Kuantan Pahang, Malaysia - Swe, Swe Latt; Mohd Rus, Razman; Ab Rahman, Jamalludin; Tin, Myo Han; Htike, Myat Phyu; Nasreen, Hashima E; Abd. Aziz, Karimah Hanim (2015)
Background: The vast majority of smokers want to quit and most make repeated attempts to do so. Although, effective treatment for nicotine dependence (ND) is present now, repeatedly fail to quit is still a common issue among smokers because of beyond nicotine addiction. Objective: To measure nicotine dependence (ND) level among adult male smokers and influences of socio-economic (SE) characteristics on ND and failing to quit smoking. Methods: A cross-sectional descriptive and analytical study was conducted in 2015 among 156 current adult male smokers in Kuantan, Malaysia. Socio-demographic and economic status, history of smoking and quitting attempt within 12 months and reasons for failing quit were identified by using a self-administered questionnaire. Level of nicotine dependence was assessed by validated Malay version of Fagerstrom Test for Nicotine Dependence questionnaires. Influence of socio-demographic and economic status on attempt to quit smoking and level of ND was analyzed. Results: Prevalence of low, moderate and high nicotine dependence level were 69.9%, 28.2% and 1.9% respectively. Among them, 55.1% were tried to quit smoking during 12 months. The most of reasons to fail quit attempt were nicotine addiction (69.8%) followed by uncomfortable/ tension/ not alert (10.5%), peer smoking/ social (10.5%), feel sleepy (7.9%) and desire to eat a lot (1.3%). Married smokers (56.6%) aged 31-40 years old (66%) with secondary education (52.9%) , private employee (68.3%), 1000-3000 RM family income per month (58.1%), and low ND score (59.6%) were tried to quit attempt and failed to quit. Smokers with low mean ND score (2.93) were attempted to quit significantly than those with high mean ND score (3.73). Conclusion: Nicotine dependence as a main reason for failing to quit smoking was confirmed in the study; however, influence of socio-demographic and economic characteristics was highlighted to consider in plan for successful quit smoking.